The Potential for Counselling to Facilitate Intergenerational Dialogue and Knowledge Transfer Related to Land Rights, Traditional Practices and Sustainable Land Use in Nigeria - Mustapha, Mulikat Ladi Abdulqadir; Okesina, Falilat Anike (Journal of Law, Society and Development, 2025)
The transfer of knowledge between generations is crucial to maintaining traditional land rights, practices and sustainable land use in rural communities in Nigeria. This article explores the potential of extension intervention to facilitate intergenerational dialogue, transfer of sustainable land management knowledge and it argues that consultations can be a safe and inclusive platform to share experiences and exchange knowledge. It discusses the potential of narrative therapy and memory techniques to evoke and preserve traditional stories, wisdom and practical land-related stewardship. It emphasises the importance of integrating indigenous knowledge systems and culturally relevant practices into counselling interventions. It also highlights the role of counselling in addressing generational conflicts, trauma and historical land-related dispossession injustices.